Antiproliferative effect of boldine on neural progenitor cells and on glioblastoma cells - Jiménez-Madrona, Enrique; Morado-Díaz, Camilo J.; Talaverón, Rocío; Tabernero, Arantxa; Pastor, Angel M.; Sáez, Juan C.; Matarredona, Esperanza R. (Frontiers in Neuroscience, 2023)
The subventricular zone (SVZ) is a brain region that contains neural stem cells and progenitor cells (NSCs/NPCs) from which new neurons and glial cells are formed during adulthood in mammals. Recent data indicate that SVZ NSCs are the cell type that acquires the initial tumorigenic mutation in glioblastoma (GBM), the most aggressive form of malignant glioma. NSCs/NPCs of the SVZ present hemichannel activity whose function has not yet been fully elucidated. In this work, we aimed to analyze whether hemichannel-mediated communication affects proliferation of SVZ NPCs and GBM cells. For that purpose, we used boldine, an alkaloid derived from the boldo tree (Peumus boldus), that inhibits connexin and pannexin hemichannels, but without affecting gap junctional communication. Boldine treatment (50 µM) of SVZ NPCs grown as neurospheres effectively inhibited dye uptake through hemichannels and induced a significant reduction in neurosphere diameter and in bromodeoxyuridine (BrdU) incorporation. However, the differentiation pattern was not modified by the treatment. Experiments with specific blockers for hemichannels formed by connexin subunits (D4) or pannexin 1 (probenecid) revealed that probenecid, but not D4, produced a decrease in BrdU incorporation similar to that obtained with boldine. These results suggest that inhibition of pannexin 1 hemichannels could be partially responsible for the antiproliferative effect of boldine on SVZ NPCs. Analysis of the effect of boldine (25 to 600 µM) on different types of primary human GBM cells (GBM59, GBM96, and U87-MG) showed a dose-dependent decrease in GBM cell growth. Boldine treatment also induced a significant inhibition of hemichannel activity in GBM cells. Altogether, we provide evidence of an antimitotic action of boldine in SVZ NPCs and in GBM cells which may be due, at least in part, to its hemichannel blocking function. These results could be of relevance for future possible strategies in GBM aimed to suppress the proliferation of mutated NSCs or glioma stem cells that might remain in the brain after tumor resection.